A conceptual framework for relationship between symbolic risk consumption with Electronic Word of Mouth - Dien Mardhiyah, Sri Hartini,; ., Sukaris (Opción, 2020)
The study aims to investigate a conceptual framework for the relationship between symbolic risk consumption with Electronic Word of Mouth (EWOM) to experience sharing via comparative qualitative research methods. As a result, epistemic value is created when a product arouses curiosity, gives new things and or satisfies the desire of knowledge. In conclusion, businesses can implement the findings of this study to improve destination management which prioritizes the value that tourists will get when visiting a destination.